Introduction to drug metabolism enzymes - Smith, Dennis (Henry Stewart Talks, 2007)
Metabolism of lipophilic molecules, Phase I and Phase II enzymes, Location, Mechanism, Typical substrates, Genetic variation, Species variation, Inhibition and drug interactions, Drug design
Reviewed at 2016/04/20